Personality traits of university students with smartphone addiction - Kheradmand, Ali; Amirlatifi, Elham Sadat; Rahbar, Zahra (Frontiers in Psychiatry, 2023)
Background: Nowadays smartphone use is increasing drastically. There is a higher prevalence of smartphone addiction in some specific personality traits. Objectives: The goal of this study is to evaluate the association of smartphone addiction with personality traits. Methods: This study is correlational research. 382 students of Tehran universities were asked to answer the smartphone addiction scale (SAS) questionnaire and the Persian version of Cloninger temperament and character inventory (TCI) questionnaire. After the assessment of the smartphone addiction questionnaire, individuals with smartphone addiction were identified and then compared to the non-smartphone addicted group in terms of personality traits. Results: 110 individuals (28.8%) were prone to smartphone addiction. Mean scores of people with smartphone addiction were higher in novelty-seeking, harm avoidance, and self-transcendence than the non-addicts and were statistically significant. In persistence and self-directedness mean scores of the smartphone addiction group were lower than the non-addicts and they were statistically significant. Individuals with smartphone addiction had higher reward dependence and lower cooperativeness however they were not statistically significant. Conclusions: high novelty seeking, harm avoidance, self-transcendence, low persistence, and self-directedness which indicate narcissistic personality disorder, could have a role in smartphone addiction.